Resettlement Interventions for Internally Displaced Persons in Northern Uganda - Ogwang, Tom (IJRSS & K.A.J, 2014)
There were 1.8 million internally displaced persons (IDPs) in greater northern Uganda at the height of the LRA insurgency, from 1994 to mid-2000. 1 Although the 2006 Juba peace talks were ultimately unsuccessful at bringing about a resolution to the conflict, it did contribute to a semblance of relative calm and peace in the northern, enabling many people to leave the official IDP camps for either their original homes or ‘transit’ camps. The government of Uganda and development partners embarked on resettling and rebuilding war ravaged areas of that country through various intervention programmes, including resettlement interventions of internally displaced persons in northern Uganda. Given the spectrum of experiences associated with return, resettlement, and reintegration of displaced persons, it is imperative to ask whether the interventions designed and developed actually address the needs of the displaced persons.
Resettling and rebuilding war ravaged areas.
Keywords: Resettlement, internally displaced persons